2008
DOI: 10.1212/01.wnl.0000327671.91357.96
|View full text |Cite
|
Sign up to set email alerts
|

Natalizumab disproportionately increases circulating pre-B and B cells in multiple sclerosis

Abstract: Circulating B cells and especially pre-B cells are most prominently elevated among the studied immune cell subsets, raising the possibility that the effects and side effects of natalizumab are partly mediated by actions on B cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
128
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(149 citation statements)
references
References 23 publications
17
128
0
4
Order By: Relevance
“…Natalizumab treatment has been shown to reduce the migration of leukocytes into the CNS [1,6,11,16,17], to inhibit the retention of memory-and marginal zone-like B cells within the spleen [6] and to induce a sequestration of lymphocytes, in particular activated T cells [18], and of immature B cells [4] in the peripheral circulation of MS-treated patients. However, considering the scarcity of leukocytes in the CNS compared to the periphery and the slight contribution of memory-and marginal zone-like B cells on the composition of the lymphocyte pool, it is unlikely that the reduced migration of leukocytes into the CNS and the decreased retention of specific B-cell subsets in the spleen can quantitatively affect peripheral lymphocyte count or fully explain the increase of lymphocytes observed during natalizumab therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Natalizumab treatment has been shown to reduce the migration of leukocytes into the CNS [1,6,11,16,17], to inhibit the retention of memory-and marginal zone-like B cells within the spleen [6] and to induce a sequestration of lymphocytes, in particular activated T cells [18], and of immature B cells [4] in the peripheral circulation of MS-treated patients. However, considering the scarcity of leukocytes in the CNS compared to the periphery and the slight contribution of memory-and marginal zone-like B cells on the composition of the lymphocyte pool, it is unlikely that the reduced migration of leukocytes into the CNS and the decreased retention of specific B-cell subsets in the spleen can quantitatively affect peripheral lymphocyte count or fully explain the increase of lymphocytes observed during natalizumab therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Its mechanism of action is thought to be mediated through the block of the binding between the α4 subunit of the α4β1 (very late antigen-4; VLA-4) and α4β7 integrins on the lymphocytes of systemic circulation with their ligand, the vascular cell adhesion molecule 1 (VCAM-1), on vascular endothelium. Natalizumab also induces a continuous decrease of α4 expression [3] that results in a reduced transmigration of inflammatory cells across the bloodbrain barrier (BBB) into the central nervous system (CNS) and in an enhancement of the number of B cells, in particular immature B lymphocytes, CD8 + , CD4 + and NK cells in peripheral blood [4][5][6][7]. In treated patients, the increase of CD34 + precursor cells [8], together with the transient increase of nucleated immature red cells [9] and immature B lymphocytes [4] has suggested that natalizumab can preferentially mobilize immature cell subsets, probably because of its interference with the binding between VLA-4 and the VCAM-1 on the bone marrow (BM) stromal cells [8].…”
Section: Introductionmentioning
confidence: 99%
“…Correspondence: Dr. Mireia Sospedra e-mail: Mireia.SospedraRamos@usz.ch in T-, NK-and especially B cells and a decrease in monocytes [9][10][11][12]. These changes have been attributed to a higher release of hematopoietic precursor cells from the BM as well as a reduced migration of leukocytes into the central nervous system (CNS).…”
Section: Introductionmentioning
confidence: 99%
“…2 Secondary effects of natalizumab include mild leukocytosis with lymphocytosis and decreased numbers of B and T lymphocytes in the cerebrospinal fluid, 3 but have been poorly investigated. 4 We checked the peripheral blood lymphocytes of seven patients (from a series of 10) 5 treatment and demonstrated an increase of immature B cells with a particular pattern of adhesion molecules. All patients had relapsing-remitting MS and were treated with natalizumab according to standard procedures, that is, 300 mg intravenously once a month.…”
mentioning
confidence: 99%